Effectiveness of Tableau and SQL Software in Analytics in Business Decisions - Janani. S; Manoj Kumar. S; Akash. S. Bilagi; Prof. Sunetra Chatterjee (International Journal of Engineering and Management Research, 2023)
The ability to raise, manage and examine the data gathered by multiple people around the library is provided by data images to librarians. This article discusses the Ohio State University Libraries' experiences with Tableau, sophisticated information management, and quick analytics solutions. Tableau enables the librarian to combine and make use of data gathered from various sources, as well as deal with logs, Google Analytics, and usage reports for e-resources. In addition to sharing visualization examples, the essay explains the backdrop for including information graphics in The Ohio State University Libraries' assessment program. The benefits of combining and viewing information visualizations from various sources are described and investigated. The paper is ended with a brief discussion of the potential future developments for using Tableau Desktop to visualize library information.